Clinico-radiological profile and outcome of patients undergoing intercostal tube drainage in a tertiary care hospital in West Bengal, India - Hassan, Md Ikbal; Dr. Saswata Ghosh; Agarwalla, Ajay; Mandal, Animesh (International Journal of Medical Research and Review, 2019)
Introduction: Evacuation of empyema which was first performed centuries ago, marked the beginning of thoracic drainage. The subsequent acquisition of a greater knowledge of the anatomy, physiology, and pathology of the pleural space directed the design of thoracic catheters and drainage systems and the development of the methods by which they are used. Thoracic drainage systems are designed to remove air and liquids from the pleural space or mediastinum, which collect there as a result of injury, disease, or surgical procedures. Method: A total of 100 patients who underwent intercostal tube drainage due to various etiologies are followed up for 3 months in the study Results: In this study it was observed that pneumothorax (67%) as the most common indication for chest drain insertion followed by hydro-pneumothorax. During this period 100 patients of different pathologies related to chest underwent chest intubations. Amongst them 88(88%) were male and 12(12%) were female. Subcutaneous emphysema was found to be the most common complication followed by ICD tube blockage. Among the study population 95% patients were successfully treated & unsuccessful outcome was only 5%. Conclusion: Chest tube insertion is a common procedure usually done for the purpose of draining accumulated air or fluid in the pleural cavity. Small-bore chest tubes (≤14F) are generally recommended as the first-line therapy for spontaneous pneumothorax in non-ventilated patients and pleural effusions in general. Large-bore chest drains may be useful for very large air leaks, as well as post-ineffective trial with small-bore drains.